Readiness of the Czech Market for Big Data - Žáčková, Kristýna (2018)
The goal of the thesis is finding the connectivity between usage of Big Data and business sectors and retrieving insights about the specifics of its usage in these industries on the Czech market. The main insights examined are the usage and way of storing Big Data, solutions for its analysis and the most common problems businesses face regarding Big Data. The thesis consists of summary of the main methods of usage and current technologies from available literature, which is followed by explanation of quantitative research and why this research was not successful. The results about current solutions for Big Data storage and analysis and the connected challenges have been retrieved by 10 interviews carried out with professionals from different positions and business sectors. The qualitative research has retrieved sufficient information for understanding of available popular solutions and common problems to avoid, while not being able to quantify the usage according to industries. While the interviewed companies use Big Data for Marketing, as a core product, price setting or operations, the options are much wider and not leveraged. Hadoop cannot be used for real-time analysis and technical companies rather create their own code. Companies struggle with lack of employees educated in business as well as data analysis, lack of time due to focus on GDPR, IT espionage and others.